IMPROVING THE MECHANISM FOR DEVELOPING LEADERSHIP QUALITIES OF FUTURE TEACHERS IN HIGHER PEDAGOGICAL EDUCATION INSTITUTIONS (World Bulletin of Education and Learning, 2026)
This article identifies effective ways to develop leadership competencies in future teachers based on modern pedagogical approaches. In particular, the importance of implementing innovative technologies in the educational process, developing reflective activities, and fostering communicative and social competencies is substantiated. In addition, the study proposes a comprehensive mechanism for developing teacher leadership, systematically describing its structural components, stages, and implementation conditions. The effectiveness of the proposed mechanism is confirmed through empirical analysis. The findings of the study contribute to improving the professional training of future teachers in higher pedagogical education, enhancing their leadership potential, and improving the overall quality of education.
Keywords: Teacher leadership, systematic review, education, methodological quality assessment.